USING MEMBRANE AND NANO TECHNOLOGIES IN WATER PURIFICATION SYSTEMS IN REGIONS WITH HIGH SALINE LEVELS - Raihan Yusupovna Kalimbetova (Modern American Journals, 2025)
This article examines the application of membrane and nanotechnologies in water purification systems in regions of Uzbekistan experiencing high levels of salinity. The research highlights the urgent need for advanced water treatment solutions in arid and semi-arid zones, particularly in areas such as Karakalpakstan and Khorezm, where groundwater is often saline or brackish. The article explores the advantages of reverse osmosis, nanofiltration, and emerging nano-based filtration materials in improving water quality, ensuring the safety of drinking water, and reducing health risks. The study also discusses the economic feasibility and environmental sustainability of these technologies in local contexts.
Keywords: water purification, nanotechnology, membrane filtration, reverse osmosis, salinity, sustainable solutions, brackish water, environmental safety, clean water access, nano-membranes, desalination, eco-technologies, water scarcity.